Student engagement in a fully online accounting module: An action research study - Malan, M. (South African Journal of Higher Education, 2020)
Student engagement is crucial for learning, and especially so in online learning. For a student to be a successful online learner, they need to engage with the online content, with their peers and with the educator. This article presents an accounting module of a fully online degree where engagement was purposefully integrated using an online engagement framework. Within this framework, the educator regularly interacted with the students to ensure that they were engaging with the online material and a group task was assigned where students had to collaboratively construct knowledge and display it in a video. An action research design was followed to determine the degree of engagement within the module and to improve on it for future modules. Results indicate that regular interaction did result in more students being active and ultimately successfully completing the module. Student reflections on the group task indicated that there are definite benefits in creating knowledge collaboratively although the format in which it should be presented needs to be reconsidered.